2021
DOI: 10.1186/s12966-021-01171-2
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of objectively measured physical activity and childhood overweight: longitudinal analysis of the IDEFICS/I.Family cohort

Abstract: Background Since only few longitudinal studies with appropriate study designs investigated the relationship between objectively measured physical activity (PA) and overweight, the degree PA can prevent excess weight gain in children, remains unclear. Moreover, evidence is limited on how childhood overweight determines PA during childhood. Therefore, we analyzed longitudinal trajectories of objectively measured PA and their bi-directional association with weight trajectories of children at 2- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
(89 reference statements)
0
7
1
1
Order By: Relevance
“…Although we found no clear evidence for a causal impact of physical activity, healthy diet or well-being on obesity, associations were previously found in the IDEFICS/I.Family cohort e.g. in a smaller subset using an objective accelerometer-based measure of PA [39][40][41] . Overall, our results suggested that cultural, perinatal and familial variables have direct links to obesity, unlike individually modifiable risk factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Although we found no clear evidence for a causal impact of physical activity, healthy diet or well-being on obesity, associations were previously found in the IDEFICS/I.Family cohort e.g. in a smaller subset using an objective accelerometer-based measure of PA [39][40][41] . Overall, our results suggested that cultural, perinatal and familial variables have direct links to obesity, unlike individually modifiable risk factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies that share this limitation have also found null results (Côté-Lussier et al, 2015). In contrast, a recent large-scale study that used uniaxial accelerometry found significant protective effects of moderate-to-vigorous physical activity on child weight trajectories (Sprengeler et al, 2021). Hence, survey-reported measures that do not distinguish between light, moderate and vigorous activityas used in this studymay miss the weight-reducing benefits of certain types of activity.…”
Section: Discussionmentioning
confidence: 60%
“…An apparent limitation in the present study is the number of missing cases. Attrition of the study sample is unfortunately common in longitudinal studies ( [ 68 , 69]) and when following families during the toddler years it is expected to lose participants. However, the statistical method was chosen with this limitation in mind and LMM is a flexible tool with the advantage of being able to deal with missing values [ 55 ].…”
Section: Discussionmentioning
confidence: 99%